Mixed radiation with different doses induces CCL17 to recruit CD8+T cell to exert anti-tumor effects in non-small cell lung cancer - Huang, Liuying; Wang, Duo; Xu, Muchen; Qian, Danqi; Cao, Yulin; Wu, Xiaohan; Ming, Liang; Tang, Junhui; Huang, Zhaohui; Yin, Yuan; Zhou, Leyuan (Frontiers in immunology, 2025)
Different doses of radiotherapy (RT) exert diverse effects on tumor immunity, although the precise irradiation method remains unknown. This study sought to elucidate the influence of combining different doses of RT with immune checkpoint inhibitors (ICIs) on the infiltration of CD8 T cells within tumors, thereby augmenting the anti-tumor response. Constructing a mouse model featuring bilateral lung cancer tumors subjected to high and low dose irradiation, the analysis of RNA transcriptome sequencing data and immunohistochemical validation for tumors exposed to various dosages guided the selection of the optimal low-dose irradiation scheme. Subsequently, upon the integration of immune checkpoint inhibitors (ICIs) therapy, the infiltration of immune cells within the tumor was ascertained via immunohistochemistry (IHC) and flow cytometry (FCM). Finally, through bioinformatics analysis and experimental verification, potential strategies to bolster the anti-tumor immune response were investigated. In comparison to the administration of 20Gy alone to the primary tumor, supplementing with 6Gy directed at the abscopal tumor produces a more pronounced abscopal response. The synergy of 20Gy, 6Gy, and ICIs markedly boosts the efficiency of ICIs. According to the findings from IHC and FCM studies, the triple therapy group exhibits a heightened infiltration of immune cells into the tumor, largely attributable to the augmented expression of CCL17 within the tumor under these irradiation regimens, which subsequently draws CD8+ T cells to infiltrate the tumor site, exerting cytotoxic effects. Our study shows that the combined application of 20Gy and 6Gy can enhance the infiltration of tumor CD8 T cells in mice and improve the effectiveness of immunotherapy.